Interaction of Mannose-Binding Lectin With Lipopolysaccharide Outer Core Region and Its Biological Consequences - Man-Kupisinska, Aleksandra; Swierzko, Anna S.; Maciejewska, Anna; Hoc, Monika; Rozalski, Antoni; Siwinska, Malgorzata; Lugowski, Czeslaw; Cedzynski, Maciej; Lukasiewicz, Jolanta (Frontiers in Immunology, 2018)
Lipopolysaccharide (LPS, endotoxin), the main surface antigen and virulence factor of Gram-negative bacteria, is composed of lipid A, core oligosaccharide and O-specific polysaccharide regions. Each LPS region is capable of complement activation. We have demonstrated that LPS of Hafnia alvei, an opportunistic human pathogen, reacts strongly with human and murine mannose-binding lectins (MBL). Moreover, MBL-LPS interactions were detected for the majority of other Gram-negative species investigated. H. alvei was used as a model pathogen to investigate the biological consequences of these interactions. The core oligosaccharide region of H. alvei LPS was identified as the main target for human and murine MBL, especially L-glycero-D-manno-heptose (Hep) and N-acetyl-D-glucosamine (GlcNAc) residues within the outer core region. MBL-binding motifs of LPS are accessible to MBL on the surface of bacterial cells and LPS aggregates. Generally, the accessibility of outer core structures for interaction with MBL is highest during the lag phase of bacterial growth. The LPS core oligosaccharide-MBL interactions led to complement activation and also induced an anaphylactoid shock in mice. Unlike Klebsiella pneumoniae O3 LPS, robust lectin pathway activation of H. alvei LPS in vivo was mainly the result of outer core recognition by MBL; involvement of the O-specific polysaccharide is not necessary for anaphylactoid shock induction. Our results contribute to a better understanding of MBL-LPS interaction and may support development of therapeutic strategies against sepsis based on complement inhibition.